Respuesta :
Answer:
x = 3
Step-by-step explanation:
Given
4(2x - 7) = - 4 ( divide both sides by 4 )
2x - 7 = - 1 ( add 7 to both sides )
2x = 6 ( divide both sides by 2 )
x = 3
Answer:
[tex]x=3[/tex]
Step-by-step explanation:
We start off with: 4(2x – 7) = -4
We first need to get rid of the grouping symbols.
Use the distributive property:
[tex]4*2x=8x\\4*-7=-28[/tex]
[tex]8x-28=-4[/tex]
We now need to get rid of -28.
Use the addition property of equality:
[tex]8x(-28+28)=-4+28\\-4+28=24\\8x=24[/tex]
Now we have 8x=24. We need to do one more step before we get x by itself.
Use the division property of equality:
[tex]\frac{8x}{8} =\frac{24}{8} \\x=3[/tex]
So, the value of x is 3.